Filsafat Hukum sebagai Dasar Pembentukan Norma dan Prinsip Hukum - Nabilla, Anissa; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
Legal philosophy plays a fundamental role in shaping the direction and character of a national legal system. Law is not merely understood as a collection of coercive positive norms, but as a moral and rational reflection oriented toward substantive justice. This research aims to analyze how legal philosophy provides a conceptual foundation and value-based framework in the formation of legal norms and principles in Indonesia. The research method employed is normative legal research with a conceptual and philosophical approach, supported by literature studies of both classical and contemporary legal thinkers. The findings indicate that legal philosophy serves a crucial function in ensuring that every legislative product reflects ethical, moral, and humanitarian values as the essence of law itself. Philosophical values, particularly those derived from Pancasila, form the core basis for creating a legal system that is just, humanistic, and oriented toward social welfare. Therefore, the application of legal philosophy in the process of law-making not only strengthens the moral legitimacy of the national legal system but also ensures a balance between legal certainty, justice, and expediency in the practice of state and social life.